The Multiple Responses Injection Moulding Parameter Optimisation via Taguchi Method for Polypropylene-Nanoclay-Gigantochloa Scortechinii. - Mohd Hilmi Othman; Azman, Muhammad Azrai Ikram (Research Progress in Mechanical and Manufacturing Engineering, 2021)
This study describes the effects of the optimization of multiple responses of melt flow index, flexural strength, warpage, and shrinkage for the samples made from the blend of polypropylene-nanoclay and Gigantochloa Scortechinii fibre. The contents of fiber were fixed at 0wt.%, 3wt.% and 6wt.%. Processing condition selected were packing pressure, melt temperature, screw speed and filling time. The overall quality performances that need to be improved upon the optimisation were melt flow index, flexural strength, warpage, and shrinkage. This research started by drying the fibres at 120°C. After that, mixed with polypropylene, 15wt.% of polypropylene grafted maleic anhydride (compatibilizer) and 1wt.% of nanoclay. Samples with 0wt.% of fibers were also prepared for comparison purpose. The mixing process was performed by using twin screw Brabender mixer machine and the pallets were produced using used Brabender pelletizer with diameters from 1 to 4 mm. The multiple responses optimization process was accomplished by adopting the Taguchi L9 orthogonal array. Based on the results, for 0wt.% of fibre loading, the validated S/NQP was 134.8150 dBi at melt temperature 165°C, packing pressure 40%, screw speed 35% and filled time 1 second. For the result for 3wt.% of fibre loading, the validated S/NQP was 158.1919 dBi at melt temperature 170°C, packing pressure 35%, screw speed 35% and filled time 3 seconds. As for the 6wt.% of fibre loading, the validated S/NQP was 160.6451 dBi at melt temperature 175°C, packing pressure 35%, screw speed 25% and filled time 2 seconds. The most influential parameter for 0wt.% of fibre was melt temperature. However, the parameter changed to packing pressure with the presence of fibre. The existence of Gigantochloa Scortechinii fibre was also proven to affect significantly towards flexural strength, melt flow index, warpage, and shrinkage. In conclusion, the optimum values of the flexural strength, the warpage and the shrinkage for samples made from polypropylene-nanoclay-Gigantochloa Scortechinii had been achieved.